Analysis of The Influence of Leadership Empowerment on Performance Through Psychological Empowerment and Satisfactionon Functional Officer in The Office Regent of Simalungun - Sipayung, Tri Dharma; Muda, Iskandar; Silalahi, Amlys Syahputra (Universitas Pahlawan Tuanku Tambusai, 2023)
Based on the problem formulation above, the aim of this research is to: To analyze the influence of Leadership Empowerment on Performance through Psychological Empowerment and Satisfaction of Functional Officials in the Simalungun Regent's Office. In the research method used is empirical research which will test hypotheses built from theory and previous research. The research used in this research is positivism (quantitative), the population and samples were taken from functional officials in the Simalungun Regent's Office so that general conclusions can be obtained. . Meanwhile, this type of research is confirmatory research which describes the relationship between variables through hypothesis testing. Leadership Empowerment has a significant effect on Psychological Empowerment with a positive relationship direction. Based on the research results, it shows that the leadership empowerment variable can contribute to psychological empowerment. Leadership Empowerment has a significant effect on satisfaction with a positive relationship direction. Based on the research results, it shows that the leadership empowerment variable can contribute to increasing employee satisfaction. Psychological empowerment does not have a significant effect on satisfaction with a positive relationship direction. Based on the research results, it shows that the psychological empowerment variable is theoretically positive, but in reality psychological empowerment does not contribute to satisfaction. Psychological empowerment has a significant effect on performance with a positive relationship. Based on the research results, it shows that the psychological empowerment variable can contribute to improving employee performance. Satisfaction has a significant effect on performance with a positive relationship. Based on the research results, it shows that the satisfaction variable can contribute to improving employee performance. Psychological empowerment does not mediate the effect of empowering leadership on satisfaction. Leadership Empowerment does not mediate the effect of Satisfaction on Performance. Psychological empowerment does not mediate the effect of satisfaction on performance. Keyword: leadership empowerment, performance, psychological empowerment and satisfaction